The General Court Reverses Commission's Decision in H3G UK/Telefónica UK: Proposing a 'Fruits in a Bowl' to assess the competitive effects of mergers - Kalpana Tyagi (International Telecommunications Society (ITS), 2021)
The General Court recently annulled the Commission's 2016 H3G UK/Telefónica UK prohibition decision. Commission's failure to meet the Court's newly-found higher threshold demonstrating that the merger would lead to 'significant impediment to effective competition' (SIEC), and that H3G UK was an 'important competitive force' were central to the decision. Considering that on the one hand, the Court's decision is welcome as it reflects that even telecom mergers - that are heavily grounded in economics and econometric simulations - are subject to legal review; then on the other, it also reflects a 'gap'- an evident need to appreciate that economics and econometric simulations, need clear and demonstrable definitions for application by Commission and the courts, as the case may be. This article, using an inter-disciplinary methodology with insights from competition law and economics & business strategy, tries to address this gap, and in the process respectfully highlights how the absence of such a 'vocabulary' and 'structure' led to a decision by the General Court that is good in spirit, but deplorably mistaken in reasoning. Potential remedies that could have alleviated competition concerns, while preserving merger specific efficiencies are also discussed.
Keywords: 330; H3G UK/Telefónica UK; significant impediment to effective competition; important competitive force; Efficiencies; Merger Remedies; 4-to-3 Mobile telecom mergers